2020
DOI: 10.5334/gh.769
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Combined Lipid Abnormalities in Brazilian Adolescents and Its Association with Nutritional Status: Data from the Erica Study

Abstract: Background: Cardiovascular diseases are the leading cause of death in Brazil and worldwide. The growing incidence of obesity in children and adolescents and its association with lipid abnormalities may worsen this scenario, mainly in developing countries where obesity has reached epidemic levels. Dyslipidemias have several patterns, and the combination of some lipid abnormalities may have higher atherogenic potential. Objectives: To evaluate the prevalence of single or multiple combined lipid abnormalities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…Combined evidence from cohort studies indicates that, even in children, there is a direct relationship between increased weight and higher blood lipid levels. In our study, higher TG and LDL-C levels were linked to higher weight scores, which concur with data reported in other populations [13].…”
Section: Discussionsupporting
confidence: 93%
“…Combined evidence from cohort studies indicates that, even in children, there is a direct relationship between increased weight and higher blood lipid levels. In our study, higher TG and LDL-C levels were linked to higher weight scores, which concur with data reported in other populations [13].…”
Section: Discussionsupporting
confidence: 93%
“…Dyslipidemia has different patterns and is one of the most important risk factors for atherosclerotic plaque formation that begin early in life. The combination of some lipid abnormalities may have higher atherogenic potential (2). Therefore, the adaptation of a healthy lifestyle at an early age is one of the best preventative strategies in this regard (3).…”
Section: Introductionmentioning
confidence: 99%
“…The BMI level has a positive relationship with the lipid abnormalities and prevalence of combined lipid abnormalities. The BMI can be considered as an indicator for the diagnosis of dyslipidemia in adolescents (2). In this regard, another study conducted in Denmark (North-Europe) revealed that children and adolescents with obesity had increased concentrations of circulating lipids and exhibited an increased prevalence of dyslipidemia (8).…”
Section: Introductionmentioning
confidence: 99%